Factors that Affect Purchase of The Smartphone - Aureliani Handayani Syarifuddin; Tati Handayani; Pusporini Pusporini (Journal of Economics, Business, and Government Challenges, 2019)
This study aims to determine the influence of product factors, promotional factors and social factors on purchasing decisions Asus smartphone and know how the positioning based on product quality, durability and design of Asus smartphones with competitors such as Smartphone Oppo, Lenovo, and Smartfren. The population in this research is Pondok Ranji urban village. The sample size was taken 75 respondents for each measurement method. Data collection was done through questionnaires. The analytical technique is using PLS (Partial Least Square) and MDS (Multidimensional Scaling). The results of this study indicate that the Product Factor (X1) has an insignificant effect, Promotion Factor (X2) has a significant effect and Social Factor (X3) has an insignificant effect. Then Asus's superior positioning results on Product Quality seen from the perceptual map.